KARAKTERISASI DAN ANALISIS BENTONIT ALAM SEBAGAI BAHAN PENGISI KOMPOSIT - Ferry Rahmat A. Bukit; Erna Frida; Nurdin Bukit; Bunga Fisikanta Bukit (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
This study aims to determine the effectiveness of bentonite in the calcination process, ball mill and coprecipitation process and synthesis with the surfactant Cetyl Trimethyl Ammonium Bromide (CTAB). Calcination process at a temperature of 700oC for 5 hours, the ball mill process for 10 hours with a rotation of 250 rpm. And the coprecipitation method was carried out with 5M HCl and NaOH precipitate,and continued to be synthesized with CTAB solution. from XRD analysis for bentonite with HCL5M activation obtained particle size of 8.89 nm with a trigonal crystal system, XRF analysis contained 57.1% SiO2 content, while for bentonite synthesized with CTAB obtained 10.57 nm SiO2 content of 51.1%, the results of morphological analysis showed homogeneous particle distribution. The FTIR spectrum for bentonite showed the presence of an absorption band at 3636.93cm-1 which could be attributed to Al-OH or Si-OH stretching.